Central Giant Cell Granuloma - A Case Report - Mandeep Kaur; Rajeshwari; B Balaji Rao; G P Mamatha (Wolters Kluwer Medknow Publications, 2003)
A patient is presented with central giant cell granulorna (CGCG) of the anterior mandible along with a brief discussion on the various treatment modalities in light of the current literature. The case is reported with clinical, radiological, histological and surgical aspects of the lesion.